Human Trafficking and Slavery in the Muslim World: Islamic Law and Human Rights Advocacy as Key Factors in Eradicating this Millenary Practice - Joseph Abraham Levi (CV. FOUNDAE, 2025)
This study examines the historical evolution and contemporary manifestations of slavery and human trafficking in the Muslim world by integrating historical analysis, Islamic legal interpretation, and modern human rights perspectives. The research addresses the central problem of the persistence of exploitative practices such as forced labor, child exploitation, and coercive religious or educational systems despite the ethical and legal principles within Islam that emphasize human dignity and freedom. Using a qualitative documentary method, the study analyzes pre-Islamic practices, early Islamic reforms, classical legal traditions, and current forms of exploitation in Muslim-majority societies. Findings reveal that slavery in pre-Islamic Arabia was deeply embedded within regional social structures, but Islam introduced significant moral and legal reforms that promoted humane treatment and encouraged emancipation. However, variations in cultural and political contexts across regions allowed certain practices to persist. In the modern era, new forms of human trafficking continue to challenge both legal frameworks and societal norms. The study concludes that Islamic teachings, when understood through their historical and ethical trajectory, provide a strong foundation for eliminating all forms of human exploitation. It also highlights the importance of contemporary legal interpretations that reject slavery entirely and call for greater alignment between Islamic principles and modern human rights standards.